2018
DOI: 10.1111/cns.13051
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel immune‐relevant drug target genes for Alzheimer's Disease by combining ontology inference with network analysis

Abstract: The well-reproducible results showed the good performance of the combinatorial approach, and the remaining five new targets could be a good starting point for our understanding of the pathogenesis and drug discovery of AD. Moreover, this study supported validity of the combinatorial approach integrating ontology inference with network analysis in the discovery of novel drug target for neurological diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 103 publications
(103 reference statements)
1
13
0
Order By: Relevance
“…Eighteen potential drug target genes were identified, and thirteen of them had been reported to be closely associated with AD. Enrichment analyses of these identified drug target genes, based on nine pathway-related databases, revealed that four of those identified drug target genes are involved in the classical complement pathway and the process of presenting antigens [ 43 ].…”
Section: C Onversion To Admentioning
confidence: 99%
“…Eighteen potential drug target genes were identified, and thirteen of them had been reported to be closely associated with AD. Enrichment analyses of these identified drug target genes, based on nine pathway-related databases, revealed that four of those identified drug target genes are involved in the classical complement pathway and the process of presenting antigens [ 43 ].…”
Section: C Onversion To Admentioning
confidence: 99%
“…As reported, the human PPI network properties and biological system profile were key factors determining efficacy-safety balance (Zheng et al, 2006 ; Ragusa et al, 2010 ; Guo et al, 2018 ). Network properties were inherent feature of a target in the human PPI network, while biological system profile could reflect both the on-target and off-target pharmacology (Bender et al, 2007 ; Han et al, 2018 ; Zhu et al, 2018 ). Herein, 32 features of human PPI network together with 4 biological system properties were therefore adopted and calculated for further analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Han et al [9], harnessed the power of ontology inferencing combined with network analysis to identify new immunerelevant drug-target genes for Alzheimer's Disease (AD). This was working on the theory that due to the strong relation of AD to the immune system, there were potentially undiscovered immune-relevant AD drug-target genes that could help combat the disease.…”
Section: Semantic Applications In Drug Discoverymentioning
confidence: 99%
“…There has been a wave of computation-based innovation around creating tools to aid drug discovery [8,9,10] and many of these tools utilize semantic web technologies. This is both due to data management capabilities of the semantic tools coupled with the researcher's recognition that purely integrating sources together is not enough.…”
Section: Introductionmentioning
confidence: 99%